(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Writing professional and scientific papers is a critical task for researchers. We face several challenges in doing so, which is why we asked ourselves the research question, "How can we write professional or scientific work to be as efficient and effective as possible?". Purpose: The purpose and aim of this article is to collect rules and recommendations for writing professional and scientific papers appropriately. Method: We have used as a method the findings of methodologists and researchers, and our own knowledge and experience in researching and writing professional and scientific papers. Results: The results are a systematic set of recommendations and rules according to the different sections and to the IMRaD standard. Organization: The set of recommendations and rules is particularly useful for educational and research organizations, or their researchers. Society: At the societal level, innovation is of strategic importance and the writing of professional and scientific papers contributes innovation. Originality: The originality of the article is the concept of a "short guide" to writing professional and scientific papers. Limitations/Future Research: Further research needs to go towards more in-depth approaches and techniques of research methods and the writing of professional and scientific papers.